Contribuição ao conhecimento químico e biológico de espécies da flora paraibana: Xylopia langsdorffiana e Maytenus distichophylla - Esmeraldo, Paula Ferreira dos Santos (2015)
Phytochemical studies with Xylopia langsdorffiana (Annonaceae), have described isolation of trachylobane, atisane, kaurane, and labdane diterpenes, from the leaves, fruits, stems and roots of the species. Maytenus distichophylla (Celastraceae), popularly known as espinheira santa – (sacred thorn bush), is used in folk medicine to treat stomach ulcers, and data from the literature report the isolation of triterpenoids friedelane, and pyrimidine sesquiterpene alkaloids. Computer aided drug design brings optimizing techniques that facilitate the discovery of new drugs, offering features that allow the connection of compounds to known proteins in three dimensions, and the resulting models are able to predict reliable experimental values for biologically active molecules, making the search for biologically active compounds more efficient. Our work associated experimental tests and computational investigations based on plants selected from the Paraiban flora: X. langsdorffiana, M. distichophylla, and other Maytenus species. We report the experimental tests performed with roots and stems of Maytenus distichophylla that enabled extraction and structural determination of flavonoids, steroids, and friedelane and lupane triterpenoids. Parallel studies were developed using computational docking, PLS, and hydrophobicity, with 15 triterpenoids isolated from Maytenus species (including M. distichophylla), and 17 diterpenes isolated from X. langsdorffiana. Further, we determined chemical compositions (by GC-MS and NMR), and modulation activity against multi-resistant bacteria. Essential oils of three X. langsdorffiana specimens were analyzed by Principal Component Analysis (PCA). Three compounds were isolated from stems of M. distichophylla by chromatographic techniques: 3-oxo-12α-hydroxyfriedelane, 30- hydroxyfriedelan-3one and 29-hydroxyfriedelan-3-one. Another four compounds were isolated from the roots: β-sitosterol, 11α-hydroxyglochidone, rigidenol and 4’-Omethylepigallocatechin, this being the first report in the species of the latter three. In the docking study, the diterpenes ent-atisan-7α-acetoxy-16α-ol, labdorfianic C acid e labdorfianic B acid had the lowest formation energy values when respectively complexed with cruzaine, CYP2C9, and COX. The triterpenoids with the lowest formation energy values when complexed with these enzymes were, 3β-hydroxy-9,12-en-ursane (cruzaine), 3,4-secofriedelan- 3-oic acid (CYP2C9) and 3-oxo-12α-hydroxyfriedelane (COX). In predicting antitumor activity, as calculated from the constructed PLS model, the diterpene labdorfianic C acid, and triterpene 3β-hydroxyfriedelane, showed the best predicted values. The majority compounds identified in the essential oils were: ent-atisan-16α-ol, germacrene D, limonene and β-pinene. The monoterpenes, β-pinene and limonene, were identified in all analyzed essential oils in different percentages. Through analysis of the essential oil of the X. langsdorffiana stem (specimen A), NMR (¹H and ¹³C) were able to identify ent-atisan-16α-ol, the first time reported for this species. Some essential oils from specimen A when modulated with oxacillin against S. aureus, decreased concentration of the antibiotic by 99%. Principal component analysis (PCA) performed with the essential oil of three X. langsdorffiana specimens allowed identifying a similarity between the chemical species A and B, and a difference in C compared to A and/or B. This result may be related to the age or size of the specimens, since they share the same geographic coordinates. The models obtained in the CADD studies of were satisfactory and generated predictive results.